2009
DOI: 10.1016/s9999-9994(09)20393-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase III Detects Cytosolic DNA and Induces Type I Interferons through the RIG-I Pathway

Abstract: SummaryType-I interferons (IFNs) are important for antiviral and autoimmune responses. Retinoic acidinduced gene I (RIG-I) and mitochondrial antiviral signaling (MAVS) proteins mediate IFN production in response to cytosolic double-stranded RNA or single-stranded RNA containing 5′-triphosphate (5′-ppp). Cytosolic B-form double-stranded DNA, such as poly(dA-dT)·poly(dA-dT) [poly(dA-dT)], can also induce IFN-β, but the underlying mechanism is unknown. Here we show that the cytosolic poly(dA-dT) DNA is converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
255
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(268 citation statements)
references
References 21 publications
8
255
2
2
Order By: Relevance
“…While MDA5 binds long double-stranded (dsRNA), RIG-I ligands are rather short and characterized by a 5′-triphosphate or a 5′-diphosphate moiety with blunt-end base pairing at the 5′-end [6][7][8]. RIG-I can also recognize viral DNA via the RNA polymerase III pathway, which transcribes DNA into 5′-triphosphate RNA [9,10]. The central mechanism of cytosolic DNA sensing involves the nucleotidyl transferase cyclic GMP-AMP synthase (cGAS), which catalyzes the synthesis of the second messenger cyclic GMP-AMP (cGAMP) following binding of cGAS to dsDNA or single-stranded DNA (ssDNA) [11,12].…”
Section: Nucleic Acid Sensing and Type I Interferon Activationmentioning
confidence: 99%
“…While MDA5 binds long double-stranded (dsRNA), RIG-I ligands are rather short and characterized by a 5′-triphosphate or a 5′-diphosphate moiety with blunt-end base pairing at the 5′-end [6][7][8]. RIG-I can also recognize viral DNA via the RNA polymerase III pathway, which transcribes DNA into 5′-triphosphate RNA [9,10]. The central mechanism of cytosolic DNA sensing involves the nucleotidyl transferase cyclic GMP-AMP synthase (cGAS), which catalyzes the synthesis of the second messenger cyclic GMP-AMP (cGAMP) following binding of cGAS to dsDNA or single-stranded DNA (ssDNA) [11,12].…”
Section: Nucleic Acid Sensing and Type I Interferon Activationmentioning
confidence: 99%
“…Kong et al first reported that RIG-I À/À mice was found to be more susceptible to infection with Escherichia coli and depletion of RIG-I by RNAi or gene targeting inhibited the LPS-induced phagocytosis of bacteria [20]. Further studies have showed that RIG-I may recognize secreted bacterial nucleic acids in cytoplasm and function in antibacterial response [18,19]. In channel catfish, the most striking up-regulation of RIG-I gene expression of the liver was observed after the Gram negative bacterium Edwardsiella ictaluri infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several DNA viruses have now been shown to activate this pathway such as herpes-simplex virus-1 [14], Adenovirus, Epstein-Barr virus [15], hepatitis B virus [16] and Vaccinia virus [17]. Surprisingly, both of the intracellular gram negative and positive bacterium including Legionella pnuemophila and listeria monocytogenes were shown to activate type I IFN responses through RIG-I signaling [18,19]. Moreover, the bacterial lipopolysaccharide has been found to induce the expression of RIG-I in both macrophages and vascular endothelial cells [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…RNA polymerase III was found to be an additional source for ligands of RIG-I. Pol III can transcribe AT-rich DNA into 5 0 -ppp RNA intermediates that can activate RIG-I [59,60]. Notably, using a specific inhibitor for RNA polymerase III, ML60218, both studies show that Epstein-Barr virus encoded non-coding RNAs (EBER) require RNA polymerase III for interferon induction that is also dependent on RIG-I.…”
Section: Role For Rig-i In the Antimicrobial Response To Viruses And mentioning
confidence: 99%
“…Notably, using a specific inhibitor for RNA polymerase III, ML60218, both studies show that Epstein-Barr virus encoded non-coding RNAs (EBER) require RNA polymerase III for interferon induction that is also dependent on RIG-I. Additionally, infection with intracellular bacteria Legionella pneumophila and Shigella flexneri also required RNA polymerase III and RIG-I for IFN activation [60,61]. These results also provide a great example of a functional collaboration between DNA sensing and RNA sensing pathways in activating antimicrobial responses in cells.…”
Section: Role For Rig-i In the Antimicrobial Response To Viruses And mentioning
confidence: 99%